European Association of Urology guidelines on laser technologies - Herrmann, T R W; Liatsikos, E N; Nagele, U; Traxer, O; Merseburger, A S (Actas urologicas españolas, 2013)
The European Association of Urology (EAU) Guidelines Office has set up a guideline working panel to analyse the scientific evidence published in the world literature on lasers in urologic practice. Review the physical background and physiologic and technical aspects of the use of lasers in urology, as well as current clinical results from these new and evolving technologies, together with recommendations for the application of lasers in urology. The primary objective of this structured presentation of the current evidence base in this area is to assist clinicians in making informed choices regarding the use of lasers in their practice. Structured literature searches using an expert consultant were designed for each section of this document. Searches were carried out in the Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, and Medline and Embase on the Dialog/DataStar platform. The controlled terminology of the respective databases was used, and both Medical Subject Headings and EMTREE were analysed for relevant entry terms. One Cochrane review was identified. Depending on the date of publication, the evidence for different laser treatments is heterogeneous. The available evidence allows treatments to be classified as safe alternatives for the treatment of bladder outlet obstruction in different clinical scenarios, such as refractory urinary retention, anticoagulation, and antiplatelet medication. Laser treatment for bladder cancer should only be used in a clinical trial setting or for patients who are not suitable for conventional treatment due to comorbidities or other complications. For the treatment of urinary stones and retrograde endoureterotomy, lasers provide a standard tool to augment the endourologic procedure. In benign prostatic obstruction (BPO), laser vaporisation, resection, or enucleation are alternative treatment options. The standard treatment for BPO remains transurethral resection of the prostate for small to moderate size prostates and open prostatectomy for large prostates. Laser energy is an optimal treatment method for disintegrating urinary stones. The use of lasers to treat bladder tumours and in laparoscopy remains investigational.